Anisotropic nanocomposite films of hydroxypropylcellulose and graphene oxide with multi-responsiveness. Issue 49 (13th September 2019) - Ying, Zhimin; Lin, Xiao Ying; Du, Cong; Zheng, Si Yu; Wu, Zi Liang; Zheng, Qiang
Abstract : Nanocomposite films fabricated by blade-coating possess anisotropic mechanical properties and multi-responsiveness to external stimuli, affording potential applications as sensors and actuators. Abstract : Anisotropic nanocomposite films of hydroxypropylcellulose (HPC) and graphene oxide (GO) were fabricated by blade-coating of the aqueous mixture to align the substance and subsequent solvent evaporation to freeze the oriented structure. Owing to the anisotropic structure, the composite films showed anisotropic mechanical properties and response to external stimuli. The influences of GO content, stretch rate, and relative humidity on the anisotropic structure and mechanical properties of the films were investigated. The incorporation of GO did not destroy the anisotropic structure of the HPC film, but improved the mechanical properties to some extent and favoured the bending deformation and locomotion of the composite film under the humidity gradient. These behaviours were associated with the large aspect ratio and excellent gas barrier property of GO nanosheets that favoured suppressing the slippage of HPC chains and enhanced the differential volume change at the top and bottom surfaces of the film. The composite HPC film with GO or reduced GO also responded to near-infrared light due to the photothermal effect and the variation of HPC matrix at a high temperature. This facile strategy should be applicable to other natural or synthetic polymers to fabricate anisotropic composite films with potential applications as optical devices, sensors, and actuators.